Mitochondrial diseases: an update - DiMauro, Salvatore (Henry Stewart Talks, 2007)
Mitochondrial functions, Energy generation via oxidative metabolism, The respiratory chain, Mitochondrial DNA (mtDNA), Mitochondrial genetics, A genetic classification of the mitochondrial diseases, Diseases due to mutations in mtDNA, mtDNA mutations impairing mitochondrial protein synthesis, mtDNA mutations in specific protein-coding genes, Diseases due to mutations in nuclear DNA (nDNA), Mutations in nuclear genes encoding subunits of respiratory chain complexes, Mutations in nuclear genes encoding assembly proteins, Defects of intergenomic communications, Defects of the inner mitochondrial membrane lipid milieu
Archived at 2018/05/31